Real-Time IoT-Based Lecture Room Occupancy and Indoor Air Quality Monitoring System - Nur Aldira Azmee; Hazli Roslan; Suhaila Sari (Progress in Engineering Application and Technology, 2025)
A comfortable and healthy lecture room environment is essential for supporting student well-being and enhancing learning performance. However, manual monitoring of student attendance and indoor air quality is often inadequate. Unstable temperatures, poor ventilation, and elevated carbon dioxide (CO₂) levels can negatively impact comfort, health, and energy efficiency. To address this issue, this project proposes an IoT-based system that continuously monitors student presence and key environmental parameters like temperature, humidity, and CO₂ levels. The system provides a low-cost, automated solution that can be integrated into existing facility management tools. It uses an ESP32 microcontroller with PIR sensors, an SHT40 sensor for temperature and humidity, and an MQ135 sensor for gas detection. Real-time data is visualized through the Blynk mobile app and logged in Google Sheets for analysis. Target users include facility managers and university administrators seeking data-driven approaches to optimize indoor conditions. Two lecture rooms were monitored concurrently to evaluate performance. Results indicated that Bilik Kuliah 5 maintained acceptable environmental conditions, while Bilik Kuliah 6 exhibited higher temperatures and gas levels exceeding comfort thresholds. These findings highlight the system’s ability to identify areas needing improved ventilation. In conclusion, the system successfully achieved its objectives by promoting safer, healthier, and more energy-efficient learning environments. This project showcases the practical potential of IoT in improving educational facility management.